2011
DOI: 10.1007/s12283-011-0078-z
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic drag and biomechanical power of a track cyclist as a function of shoulder and torso angles

Abstract: The speed attained by a track cyclist is strongly influenced by aerodynamic drag, being the major retarding force in track events of more than 200 m. The aims of this study were to determine the effect of changes in shoulder and torso angles on the aerodynamic drag and power output of a track cyclist. The drag of three competitive track cyclists was measured in a wind tunnel at 40 kph. Changes in shoulder and torso angles were made using a custom adjustable handlebar setup. The power output was measured for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…Positions that resulted in reductions in aerodynamic drag were also related to a lower velocity deficit and turbulence levels in the wake. Studies by García-López et al [51] and Underwood et al [49] have shown that reducing the torso angle generally results in a reduction in aerodynamic drag. However, these studies also showed that minimising torso angle did not always lead to the lowest aerodynamic drag readings.…”
Section: Wind Tunnel Testing Of Rider Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positions that resulted in reductions in aerodynamic drag were also related to a lower velocity deficit and turbulence levels in the wake. Studies by García-López et al [51] and Underwood et al [49] have shown that reducing the torso angle generally results in a reduction in aerodynamic drag. However, these studies also showed that minimising torso angle did not always lead to the lowest aerodynamic drag readings.…”
Section: Wind Tunnel Testing Of Rider Positionmentioning
confidence: 99%
“…This was identified in an early wind tunnel study conducted by Kyle and Burke [3] which led them to propose a three-tier hierarchy for reducing cycling resistance: (1) the position of the rider, (2) the geometry of the bicycle (or more generally cycling equipment), and (3) the methods for minimising the rolling resistance and drive-train friction losses. Although the biomechanics and physiological efficiency of cycling are outside the scope of this review, when optimising cycling performance, the power output and fatigue characteristics of cyclists must also be weighed up against any apparent gains in the aerodynamic performance through adjustment to position [47][48][49]. Any changes to rider posture must also be considered along with current UCI rulings on legal rider positions.…”
Section: Optimising Single-rider Aerodynamicsmentioning
confidence: 99%
“…It is evident that exerting maximum power in the "Sprint low" position is less straightforward than in the "Sprint regular" position, and that the former will, therefore, require much more dedicated training. In the past, investigations concerning the relation between cyclist drag and power output were performed by Grappe et al [44], Underwood et al [45], and Fintelman et al [46][47][48]. Future studies should definitely address the effects of different cyclist sprint positions on power and on optimizing aerodynamic drag and power output.…”
Section: Limitations and Further Workmentioning
confidence: 99%
“…Underwood et al [22] investigated if a cyclist's drag could be minimised with changes in torso and shoulder angles. Wind tunnel experiments at 40 km/h were conducted with three competitive track cyclists, using a custom handlebar setup for repeatability and measurability.…”
Section: Introductionmentioning
confidence: 99%